GAMBARAN PENGETAHUAN ORANG TUA DAN PERILAKU MEMBERSIHKAN LIANG TELINGA ANAK DENGAN KEJADIAN IMPAKSI SERUMEN PADA ANAK SEKOLAH DASAR DI WILAYAH PESISIR (Studi Kasus Pada Anak Kelas 1 di Lima Sekolah Dasar, Wilayah Kerja Puskesmas Bandarharjo, Semarang Utara) - Hafidzoh Najwati; Lintang Dian Saraswati; Muyassaroh Muyassaroh (Jurnal Kesehatan Masyarakat (Undip), 2017)
Cerumen impaction is a cerumen accumulation that covers one-third of the ear canal unilaterally or bilaterally, accompanied by symptoms or without symptoms.The incidence of cerumen impaction in 1st grade elementary school in the coastal area, Bandarharjo Health Center work area was 18.34% (2015) and increased to 32.77% (2016). Untreatedcerumen impaction has the potential to cause hearing loss, thus disrupting the process of absorption of school children's learning.This study aims to describe the proportion of incidence of cerumen impaction, parent’s knowledgeand behavior of cleaningthe child's ear canal. This study is a descriptive observational study with crosssectional study design conducted on 262  1st graderof five elementary schools as a sample by giving questionnaires to parents of children as respondents. The selection of the sample is done by simple random sampling to determine the name of the school and by sample frame listing to determine the child's name. 50,8% children suffering from cerumen impaction, and 49,2% is normal. The proportion of good knowledgeable parents is 52.7%, almost the same as the less knowledgeable parents(47.3%). The majority of parents (85,1%) used cotton buds to clean the child's ear canal, and 51.5% parents cleaned the child's ear canal by one-week frequency. In order to prevent the incidence of cerumen impaction in children, it is requiredto educate the parents about cerumen characteristics, cerumen function,not to use hard ear cleaning tool, and not to clean the child's ear canaleveryday.